Characterization, analysis, and recommendations for minimization of microplastics in Makati City creeks - Lumongsod, Stephanie Lou R.
This study investigates microplastic contamination in three Makati City creeks draining to the Manila Bay: Makati Diversion Channel, Bangkal Creek, and Maricaban Creek. For each sampling point, 60 L of creek water was passed through stacked sieves (4.76 mm, 0.800 mm, and 0.300 mm). Samples collected were subjected to wet peroxide oxidation and density separation by NaCl flotation. Suspected particles were thereafter classified under a 30x magnification-dissecting microscope. 24 samples were selected for validation and polymer identification using FTIR. The investigation confirms the presence of microplastic debris in all sampling points, in the form of polypropylene (PP), polyethylene (PE), and polyethylene terephthalate (PET). The collection of deris comprise fragments, fibers, and films; suggesting that they are secondary in nature. In addition, field surveys were conducted across Makati City's 33 barangays to examine waste generation and disposal practices, awareness on local policies, and participation. Respondents comprise 33 barangay staff members and 189 household residents. 91.01% said that they use and dispose plastics at their households and 61.38% practice waste segragation at source. They study recommends program to minimiza the leakage of plastics to water bodies.